Rancang Bangun Sistem Informasi Perpustakaan Sekolah Berbasis Web Guna Meningkatkan Efektivitas Layanan Pustakawan - Dani Anggoro; Ahmad Hidayat (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
The library is a facility that serves as a support for student and teacher learning activities. The Library's collection is a textbook that is made a reference to the learning process. In managing data and information, the Library of SMP Negeri 28 Tangerang uses conventional way. This makes the librarian difficult to process data and to display effective information. The purpose of this research makes designing a Web-based library information system to help librarians solve problems in school libraries. Observations, interviews and literature studies are methods used to collect data (need analysis). Meanwhile, prototypes were used to build the school library information System. The result of designing the school library information system is tested using black box testing. The results of this system activity's data, designed the school library information System and the results of information system evaluation. Activity Data in the show in system analysis is running. Design builds an information system is displayed with business process, UML diagram and screen view of a web-based information system. The results of the evaluation indicate that the school library information system can perform fast browsing of data and the information shown in the form of reports is accurate.